Advantages and disadvantages of deep soil mixing versus stone columns in soft soil - Einarsson, Sofia; Persson, Linda (My University, 2024)
Urbanization has lead to a scarcity of suitable land for new infrastructure, resulting in constructions being built on unsuitable soft soil. To counter this, deep foundations and ground improvement techniques are used to enhance the stiffness and strength of the soil and mitigate risks. There is also a growing emphasis on sustainable construction to reduce the carbon foot print. The aim of this thesis was to investigate the differences between deep soil mixing and stone columns to understand the advantages and disadvantages with the methods. To accomplish this aim both a literature review and numerical analyses was conducted. The literature review focused on giving relevant background to the methods. The review covers an introduction to ground improvement followed by more detailed chapters about deep soil mixing and stone columns, including general information, different applications and the installation process as well as some specific details related to each method. The numerical analyses were conducted in Plaxis 2D using a unit cell approach. The analyses were carried out for end-bearing columns with parameters from two distinct locations, Östra berg and Väg 160. The aim of the numerical analyses were to evaluate the differences between the methods, as well as the impact of different aspects including ground conditions, embankment height and cc-spacing. The results of the numerical analyses showed that deep soil mixing is slightly more effective for reducing final settlements. However, considering other aspects such as rate of consolidation, stone columns are more favourable. The high permeability in the stone columns accelerates the settlements leading to increased settlements during construction and decreased post-construction settlements. In addition to the numerical analyses described above a sensitivity analysis was conducted. The sensitivity analysis showed that the parameters that the model is most sensitive to are permeability and preconsolidation pressure, thus OCR or POP. The results from the literature study showed that the main advantage with stone columns are the smaller environmental impact compared to deep soil mixing, which is also strengthened with the simplified carbon calculation made as part of this project. The main advantage with deep soil mixing is the extensive knowledge about the method and its successful application in many projects in Sweden.
Keywords: Deep soil mixing; Stone columns; Soft soil creep; Numerical analysis; Ground improvement; Unit cell